Apropriação privada e valorização imobiliária na “Orla” de Palmas-TO: onde e quando os projetos disfarçam os verdadeiros planos - Vieira, Kássia da Costa (Universidade Federal do Tocantins, 2019)
This dissertation seeks to understand the changes in the use and occupation of the area between Parque avenue and the banks of the Luís Eduardo Magalhães hydropower plant (HPP) reservoir in Palmas, capital of the state of Tocantins, which, in the urban plan, appears as an Area of Leisure and Culture (ALC). To be discussed first are the changes that culminated, in spite of the initial projection of social and collective use, in the imposition and predominance of the market value, above all in the implementation of the Orla (waterfront) Project, with its respective developments, which included the incorporation of the remaining areas on the banks of the reservoir; then, the new projects proposed for this area are highlighted. To this end, the operationalization of this research is supported by bibliographical, documentary and field surveys, with analysis and interpretation supported by interdisciplinary and socioenvironmental perspectives. At the time of the development of the urban project, in 1989, the first interests with regard to ALC emerge. The changes began to occur with the first municipal urban laws in 1991 and 1993. But, with the beginning of the development of the aforementioned plant in 1998, the first urban projects for this area appear, commissioned by the state government and named ''Orla Project''. In order to ensure its implementation, the state government institutionalized this project in 2000 by way of law, and established a public-private partnership in 2001 with local construction companies, through which the company Orla Participações e Investimentos PLC was founded, a company whose main objective is to enable the implementation of the Orla Project developed in 2002 by GrupoQuatro, in the block ALC SO14 and part of the block ALC SO 34, with the approval of the Orla 14 allotment, implying the transfer of public lands to the private domain and drastic change of use, marked by the change from the social and collective use in the initial proposal, to market value. Since the implementation of the Orla Project, with a tendency for increasing land and property valuation, the interests in the ALC are growing, with new changes and readaptations, in the other areas on the banks of the reservoir, both in the south and north urban areas. More recently, new projects have emerged – some with the characteristics of large urban projects, idealized by both public and private agents. Thus, such projects have triggered drastic metamorphoses in the uses projected for this area of the city, giving it new socio-spatial contents, due to the alteration of the nature of this part of the urban space, that modifies the form and the uses of the area and confirms the contradictions between the use value and the market value of urban land.